Negotiation and resistance : peasant agency in high Medieval France - Bouchard, Constance Brittain (Cornell University Press, 2022)
"This book is about how the peasants of northern France in the high Middle Ages, ca. 1000-1250, exercised agency, that is, self-determination and resistance to oppression, especially through collective negotiation with the powerful, including landlords, counts, and dukes, and bishops and abbots"--